Desenvolvimento e avaliação de infográfico para pessoa com doença renal crônica em tratamento hemodialítico - Araújo, Dariane Veríssimo de (2025)
Chronic Kidney Disease (CKD) is characterized by a slow and progressive decline in kidney function. When it reaches the most advanced stage, artificial interventions such as hemodialysis (HD) become necessary. As a result, patients must take an active role in their self-care by receiving guidance on daily care during hemodialysis treatment. Educational technology serves as a strategy to support health education initiatives, led by nurses for individuals with CKD undergoing HD, focusing on self-care. This study is justified by the lack of educational technologies tailored to this specific audience—ones that address not only isolated topics but also the multiple and complex needs of CKD patients on HD. The study aims to develop an animated infographic to guide self-care for individuals with chronic kidney disease undergoing hemodialysis. The literature review covers three main topics: (1) chronic kidney disease statistics and hemodialysis as a treatment, (2) educational technologies for hemodialysis patients (based on a scoping review), and (3) academic mobility—perspectives on the transcultural adaptation of the infographic. This is a methodological study, and the infographic was developed based on the Cognitive Theory of Multimedia Learning as the theoretical framework and the ADDIE instructional design model (Analysis, Design, Development, Implementation, Evaluation) as the methodological approach. The infographic was created in five stages: analysis (literature review), design (script development), development (collaboration with a graphic designer), implementation (evaluation by experts using health education validation tools), and evaluation (using the Content Validity Index, CVI). The study received ethical approval (CAAE: 82777424.8.0000.5054, Opinion No. 7,273,336) since it involves human subjects. The final infographic has a duration of 11 minutes and 49 seconds and addresses key topics such as treatment adherence, nutrition, fluid and weight control, tips for fluid intake, hemodialysis access, medications, and multidisciplinary follow-up. The audio was recorded by the researcher to ensure a humanized tone, and the images depict patients' daily lives in an animated format to enhance engagement. After evaluation, the infographic achieved a CVI of 0.99 for content and 0.98 for appearance, confirming its validity for use in self-care guidance for hemodialysis patients. Thus, this educational tool can be effectively used with CKD patients on HD, either in its complete form or by focusing on specific topics, and can be applied in both individual and group settings.